An Analysis of Derivational Affixes in Song - Fitri Rayani Siregar; Novita Sari Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research discusses about derivational affixes in song lyrics. The researcher analyzed five songs in Harris Jung’s Salam album. The five songs are: Salam Alaikum, Good Life, Rasool’ Allah, I Promise, and My Hero. The kind of the research was library research. The researcher analyzed the data by using four steps, they are understanding (reading), identifying, classifying, and describing. The results of the research are there were two kinds of derivational affixes in Harris Jung’s Salam album in the five selected songs, they were derivational prefixes and derivational suffixes. The dominant of derivational affixes in Harris Jung’s Salam album in five selected songs were derivational suffixes with the total percantage 64% that are suffixes –ness (4), -y (1), -ful (1), -en (1), -ly (2) and then derivational prefixes with the total percantage 36% that are prefixes re- (2), un- (1), pro- (1), in- (1).